Do Caseworker Meetings Prevent Unemployment? Evidence from a Field Experiment - Pia Homrighausen; Michael Oberfichtner (Institute of Labor Economics (IZA), 2024)
Caseworker meetings have been shown to accelerate exit from unemployment. We explore whether they are also effectual before entering unemployment. In a natural field experiment, we offer caseworker meetings to workers at risk of losing their jobs while they are still employed. We find that the offer induces additional meetings and substantially shifts the first meeting forward but has no effect on entry into unemployment or on labour market outcomes within one year. The intervention does not alter jobseekers' search behaviour, which likely explains its inefficacy.
Keywords: J68; J63; J62; 330; job search assistance; caseworker meetings; job search; field experiment